An Anticoagulant Peptide from Whitmania pigra - Zhong, Shan; Yin, Yuhua; Cheng, Weiming; Yang, Depo (Asian Journal of Chemistry, 2014)
This work reports the isolation, purification and characterization of the anticoagulant peptides from W. pigra. The cold extraction solvent system used for the total bioactive components in W. pigra was acetone-water (10:90, v/v), the extracts were then subjected to gel permeation chromatography on Sephadex LH-20, Sephadex G-50 and Sephadex G-25 columns successively, affording a fraction with potent anticoagulant activity. The fraction was then undergone further chromatographic procedures. An anticoagulant named Whitmanin B was then isolated and purified from the above bioactive fraction by RP-HPLC and its molecular weight was determined as 1574.7 Da by ESI ionization time-of-flight mass spectrometry (ESI-TOF-MS) and its partial amino acid sequence were CNQSQY (I/L) R by high-resolution liquid-mass spectrometry. The isolation and purification procedure could maintain the bioactivity of the product, therefore providing an effective method for the further isolation of components for the bioactive experiments.